(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Language is a tool or medium that humans use to communicate. The Sumbawa language has a figurative language that can be used for memories or can be used to express feelings to someone. It is called proverbs. Proverbs are groups of words or sentences that convey either about someone’s condition, or about praise, satire, parables. This research is a classroom action research. In this study, the researchers used two techniques in data collection, namely documentation and observation. In analyzing the data, the researchers used three stages of data analysis, namely data reduction, data presentation and analysis, and drawing conclusions. Eleven Sumbawa language proverbs were selected as they contain the meanings of social phenomena. There were five participants in this study. From these five participants, this research can be said to be successful. Students succeeded in explaining social phenomena in English by using pictures as the media.